2012
DOI: 10.1177/1087057112447873
|View full text |Cite
|
Sign up to set email alerts
|

A Homogeneous HTRF Assay for the Identification of Inhibitors of the TWEAK-Fn14 Protein Interaction

Abstract: The TWEAK-Fn14 pathway is upregulated in models of inflammation, autoimmune diseases, and cancer. Both TWEAK and Fn14 show increased expression also in the CNS in response to different stimuli, particularly astrocytes, microglia, and neurons, leading to activation of NF-κB and release of proinflammatory cytokines. Although neutralizing antibodies against these proteins have been shown to have therapeutic efficacy in animal models of inflammation, no small-molecule therapeutics are yet available. Here, we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In regard to the first strategy, a high throughput screen measuring the effect of ~60,000 compounds on soluble TWEAK binding to the Fn14 extracellular domain was conducted by Benicchi and colleagues (129). Fifteen primary hit compounds were identified and subsequent counterassays revealed that two were potent but partial inhibitors and two were weak inhibitors (overall hit rate of 0.007%).…”
Section: Tweak/fn14 Axis-targeted Therapeutics: Additional Approachesmentioning
confidence: 99%
“…In regard to the first strategy, a high throughput screen measuring the effect of ~60,000 compounds on soluble TWEAK binding to the Fn14 extracellular domain was conducted by Benicchi and colleagues (129). Fifteen primary hit compounds were identified and subsequent counterassays revealed that two were potent but partial inhibitors and two were weak inhibitors (overall hit rate of 0.007%).…”
Section: Tweak/fn14 Axis-targeted Therapeutics: Additional Approachesmentioning
confidence: 99%
“…This risk can be mitigated by prefractionation and upfront removal of fractions with a propensity for non-stoichiometric inhibition. [70] In conclusion, state-of-the-art lead finding flowcharts appropriately combine readout-specific, target-specific and general counterscreens [55,89] to deal with the huge hit lists originating from large libraries and high hit rates. The efficacy of this approach is demonstrated by an extreme case study in which the hit list was completely annihilated by such filtering.…”
Section: Experimental Identification Of Nonstoichiometric Inhibitors mentioning
confidence: 98%
“…readout-specific and redox counterscreens. [89] The most likely reason is that the throughput of devices for dynamic [44] or static [45] light scattering is limited. NMR is also used primarily to characterize compounds synthesized during a medicinal chemistry program [50] or to confirm results by higher-throughput methods [29] rather than for screening hits at an early stage of the flowchart.…”
Section: Experimental Identification Of Nonstoichiometric Inhibitors mentioning
confidence: 99%
“…As an example of target-based primary screening, Benicchi et al 115 described a novel homogeneous time-resolved fluorescence assay to identify small-molecule inhibitors of the TWEAK-Fn14 protein-protein interaction, which is involved in activation of the NF-κB pathway in models of microglia-dependent CNS inflammation. Even though it has not yet been done, this target-based primary assay could be followed by a secondary microglial activation PA to assess the functional efficacy of identified hit compounds.…”
Section: Microglia Activation Assaysmentioning
confidence: 99%